(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Bovine fascioliasis, caused by liver flukes Fasciola hepatica and Fasciola gigantica, significantly affects cattle health and production globally. This study evaluated the prevalence and haemato-biochemical changes associated with bovine fascioliasis in 134 cattle at Katsina Central Abattoir. Using the sedimentation technique, faecal samples revealed a 3.73% infection rate, with females showing a higher prevalence (4.55%) than males (2.17%), though not statistically significant (P > 0.05). The age group 2-3 years had the highest prevalence (25.00%), with significant differences among age groups (P < 0.05). Among breeds, Wadara had the highest prevalence (20.00%) compared to White Fulani (4.93%), with a significant difference (P < 0.05). Medium-conditioned cattle showed the highest prevalence (6.67%) versus good-conditioned ones (1.37%) with significant difference (P < 0.05). Infected cattle exhibited significant reductions (P < 0.05) in packed cell volume (PCV), haemoglobin (Hb), and total erythrocyte count (RBC), as well as decreases in white blood cell count (WBC), mean cellular volume (MCV), and mean cellular haemoglobin concentration (MCHC). Biochemical analysis indicated elevated alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and total bilirubin (TB) levels (P < 0.05), with reduced albumin (ALB), total protein (TP), and conjugated bilirubin (CB) levels (P < 0.05). These results highlight the significant impact of bovine fascioliasis on cattle health in Katsina State, emphasizing the need for effective control strategies.